Work–family policies and women's job mobility: emerging divides in female workforce in Japan. Issue 4 (8th August 2022) - Nishimura, Junko
ABSTRACT: The impact of work–family policies on women's employment must be considered in the institutional context wherein policies are introduced. This study examines the impact of introducing work–family policies on job exit and change experienced by 25–45-year-old women since the 1990s in the Japanese context. The past three decades are characterised by a deepened labour market duality, continued basic social welfare framework in which labour market position is pivotal for entitlement, and intensified normative familialism. Analyses of panel data from the Japanese Panel Survey of Consumers show that with the development of work–family policies, women become less likely to leave their jobs. This phenomenon is, however, limited to women in regular employment. Mothers with pre-school-age children have not increased their labour market attachment. No change is noted in the tendency of women in regular employment being less likely to change their jobs. Results suggest that work–family policies have not only promoted women's employment but also brought divides in the female labour force. Additionally, the results indicate the importance of focusing on institutional arrangements to understand how such divides are brought about.